2022
DOI: 10.1016/j.drugpo.2021.103436
|View full text |Cite
|
Sign up to set email alerts
|

A review of the evidence on cigarettes with reduced addictiveness potential

Abstract: Background In May 2018, the Secretariat for the World Health Organization Framework Convention on Tobacco Control convened a meeting to discuss the potential for reducing the addictiveness of tobacco products. A central focus was to review research findings on the behavioral effects of reducing the addictiveness of cigarettes. Methods This manuscript reports the results of a review of the behavioral science literature, updated through April 2021, with special attention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 115 publications
2
9
0
Order By: Relevance
“…The present study is consistent with others (9, 12, 13) in being broadly reassuring about the effects of switching to very low nicotine cigarettes on mental health outcomes in those with unipolar mood and anxiety disorders, and adds the findings of reduced toxicant exposure and increased probability of successful smoking cessation when treatment is offered. A recent trial (11) that excluded smokers with serious psychiatric illness demonstrated that abrupt nicotine reduction in cigarettes is feasible.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present study is consistent with others (9, 12, 13) in being broadly reassuring about the effects of switching to very low nicotine cigarettes on mental health outcomes in those with unipolar mood and anxiety disorders, and adds the findings of reduced toxicant exposure and increased probability of successful smoking cessation when treatment is offered. A recent trial (11) that excluded smokers with serious psychiatric illness demonstrated that abrupt nicotine reduction in cigarettes is feasible.…”
Section: Discussionsupporting
confidence: 90%
“…The U.S. Food and Drug Administration (FDA) regulates tobacco products, and in 2017, announced plans to reduce the nicotine content of cigarettes to minimally addictive levels (2).While these plans remain under consideration in USA, the government of New Zealand recently announced a plan to only allow reduced nicotine cigarettes to be sold (3). Previous studies have generally found that reduction of nicotine content in cigarettes is feasible and safe in smokers with and without comorbid psychiatric illness, and it has been estimated that this would save millions of lives (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Over 25% of smokers have an affective (unipolar mood or anxiety) disorder, representing over 8 million people in the US.…”
Section: Introductionmentioning
confidence: 99%
“…Health effects derived from tobacco are mainly caused by nicotine [ 20 ]. However, many other hazardous compounds are found, regardless of the tobacco administration route (it can be smoked, chewed, or sniffed) [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years there has been increased interest in developing tobacco varieties that possess very low levels of nicotine while retaining acceptable agronomic qualities. Two of the motivating factors behind this interest include: (1) evidence from numerous clinical studies that have shown that smokers who switch to cigarettes containing nicotine levels below that capable of sustaining an addiction response will smoke less and/or find it easier to quit (reviewed in [ 1 ]); and (2) the possibility that the US Food and Drug Administration (FDA) may mandate such reductions in future cigarette products [ 2 ]. From a plant genetic perspective, lowering the nicotine content of the leaf can be accomplished through the utilization of naturally occurring mutations, genetic engineering, and genome editing [ 3 – 7 ].…”
Section: Introductionmentioning
confidence: 99%